(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Drug-resistant TB is a persistent threat, with 490 000 million cases of multidrug-resistant TB emerging in 2016.The countries with the largest numbers of MDR/RR-TB cases were China, India and the Russian Federation. Given the prolonged nature of MDR-TB, one might expect higher rates of chronic disability among cured patients with MDR-TB. To explore these questions, we conducted an observational study focusing on: clinical, bacteriological, biochemical and various health parameter status of successfully treated MDR-TB patients. Methods: Subjects enrolled in study as per inclusion and exclusion criteria were assessed by recording of demographic data and were subjected to a predetermined set of questions for determining the history of previous anti tubercular treatment and exposure to various type of risk factor for development of MDR TB. Physical parameters of health were determined and recorded. Results: Total of 84 patients were enrolled in our study (57-males, 27 females).69 subjects (46-males, 23-Females) were found apparently healthy. 25 subjects migrated outside.6 patients (male-6, Female-2) died.7 patients were diagnosed as XDR-TB (5-Males,2-Females).34 subjects (18- males, 16-females) (44.73%) were very under weight. Total 13 (Males-12, Females-1) out of 76 subjects (17.10%) were under weight. Mid arm circumference (MAC) of 35 out of 76(21- males, 18-females) subjects (46.05%) was below 5th percentile. Majority of subjects showed moderate & severe obstruction in PEFR. Conclusion: This study shows that the community based standardized treatment regimen is effective as only one of the patients was bacteriologically positive on follow up. However, significant numbers of treated MDR-TB patients suffer from clinical, nutritional and functional post-treatment adverse events leading to some morbidity.